Selected Soil Properties Among Agroforestry, Natural Forest, Traditional Agriculture, and Palm Oil Land Uses in Central Kalimantan - Rahayu, K.D.; Udawatta, R.P.; Jose, S.; Nathan, M.; Laumonier, Y.; Antonius, S. (Springer, 2021)
The deforestation in Indonesia has begun in the twentieth century due to agricultural expansion and mechanization. The uncontrolled and illegal land conversions have affected forest functions, food security, and soil health. The objective of this study is to evaluate differences in soil properties among major land-use practices and determine agroforestry’s potential for soil rehabilitation. The study design consisted of palm oil plantation (POP), traditional agriculture (TA), agroforestry homegarden (AHG), and natural forest (NF) management treatments in completely randomized block design with three replications. Soil samples were collected from three villages Kuala Pembuang, Muara Dua, and Telaga Pulang within the Rimba Raya Biodiversity Reserve located in Seruyan District, Central Kalimantan Province, Indonesia, in June 2017. Soils from 0–15 cm and 15–30 cm were analyzed for cellulase, PMEase, urease, C, and N. The results showed that enzyme activities and percentages of C and N were significantly different (α 0.05) among management practices within the soil depths. The highest enzyme activities were found in NF, AHG, and TA treatments. The lowest C level was found at 0–15 cm soil depth (1.32%) of POP. The highest nitrogen level was found at NF (1.23%) for 15–30 cm soil depth followed by TA site at 0–15 cm (1.15%). The lowest soil N level was found at POP among treatments and depths (0.43% and 0.21%). The outcomes of this study will help formulate land management recommendations for landowners, palm oil management, government agencies, and communities around the study areas to maintain soil quality for long-term sustainability of the peat forest ecosystems. Homegarden systems can be recommended as the most appropriate alternative land management in Seruyan District, Central Kalimantan. Future research could investigate microbial community structure and characteristics to understand specific soil functions by treatments.